Fixed Point Results Involving Rational Type $\mathcal{F}$-Contraction with Applications - Sonker, Smita; Sonia, (Discontinuity, Nonlinearity, and Complexity, 2026)
In this study, we employ rational expression techniques via $\mathcal{F}$-contractions to establish fixed point theorems within the context of an orthogonal complete metric space. We extend and generalize several established results from prior literature. Additionally, we provide illustrative examples to validate the robustness of our findings. Moreover, our results facilitate the determination of unique solutions for both differential and integral equations.